Démanty noci - Němec, Jan (Czechoslovakia, 1964)
Tense, brutal story of two Jewish boys who escape from a train transporting them from one concentration camp to another. Ultimately, they are hunted down by a group of old, armed home-guard members. The film goes beyond the themes of war and anti-Nazism and deals with man's struggle to preserve human dignity.
Keywords: Fiction films